Financial forecasting, analysis, and modelling : a framework for long-term forecasting - Samonas, Michael (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2015)
This book provides a complete framework of long-term financial forecasts in a practical and accessible way, helping finance professionals include uncertainty in their planning and budgeting process. With thorough coverage of financial statement simulation models and clear, concise implementation instruction, it guides readers through the entire projection plan development process. Readers learn the tools, techniques, and special considerations that increase accuracy and smooth the workflow, and develop a more robust analysis process that improves financial strategy. You will develop long-term projection plans using Excel; use appropriate models to develop a more proactive strategy; apply risk and uncertainty projections more accurately; master the Excel Scenario Manager, Sensitivity Analysis, Monte Carlo Simulation, and more. --
8.4.3.1. The Simple VBA CODE -- 8.4.4. Creating a Histogram (Frequency Distribution Chart) in Excel -- 8.4.5. Interpreting the Results -- 8.4.6. Some Issues of Concern -- Appendix -- 1. Walking through the Excel Model Provided with the Book (SteelCo SA. 4yr Business Plan) -- Introduction -- Structure of the Model -- 2. Other Excel Files Provided with the Book.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Corporations -- Finance -- Mathematical models; Corporations -- Finance -- Forecasting; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Corporations -- Finance -- Forecasting; Corporations -- Finance -- Mathematical models; Electronic books; Electronic books; Electronic books